Iodine Requirements in Pediatrics: From Fetal Life to Adolescence - Iannuzzo, Gabriella; Campanozzi, Angelo; Trevisani, Viola; Rutigliano, Irene; Abate, Veronica; Rendina, Domenico; De Filippo, Gianpaolo (Frontiers in Endocrinology, 2022)
Aim of this mini-review is to present the current knowledge on iodine requirements in the developmental age, from conception to adolescence. This is based on the analysis of updated national and international guidelines about iodine intake and prevention of iodine deficiency. The health policy initiatives that have been carried out in industrialized countries last decades, allowed a dramatic improvement of nutritional iodine status in general population. However, the prevention of iodine deficit remains an actual concern, especially for vulnerable categories, like pregnant women and adolescents.